Analisa Kuat Lentur Perkerasan Menggunakan Alat Benkelman Beam Pada Ruas Jalan Perintis Kemerdekaan - Satriyani Okbri (Jurnal Tekno Global, 2018)
AbstractThe city of Palembang as a Metropolitan city has a greater population density and it affects the increase in vehicle volume up to 20% / year. to anticipate the increase in the volume of vehicles on the Palembang Kemersungan Printis Road section, sharing the ways of the government one of them was the construction of new roads, widening roads, maintenance and repair of roads and overlays. The design of flexible pavement added thick layer that is commonly used at this time using the deflection method. The deflection method in this study uses traffic volume data which will then be analyzed to obtain the standard axle load equivalent (CESA) accumulation value over the life of the plan. Deformation values can be obtained from the Benkelman Beam tool testing results. This study aims to determine the relationship between measurements of road surface conditions with deflection values "Benkelman Beam. From the results of the survey, the level of road conditions that need to be overlaid and the deflection value in each segment is obtained, then the deflection value obtained to determine the thickness of the overlay needed. From deflection testing with the Benkelman Beam tool, an average deflection value was 0.15. Based on the graph of conceptual trigger, the value states that the Perintis Kemerdekaan road segment needs to be carried out by non-structural Routine and Additional Layer Maintenance.Keyword : Benkelman Beam, Overlay, Flexible Pavement AbstrakKota Palembang sebagai kota Metropolitan mempunyai kepadatan penduduk semakin besar dan itu mempengaruhi peningkatan volume kendaraan sampai 20% / tahun. untuk mengantisipasi pertambahan volume kendaraan pada ruas Jalan Printis Kemeredekaan Palembang, berbagi cara yang dilakukan pemerintah salah satunya pembuatan jalan baru, pelebaran jalan,permeliharaan dan perbaikan jalan serta overlay. Perencanaan tebal lapis tambah perkerasan lentur yang umum dipakai pada saat ini menggunakan metode lendutan. Metode lendutan dalam penelitian ini menggunakan data volume lalu lintas yang selanjutnya akan dianalisa untuk mendapatkan nilaiakumulasi ekivalen beban sumbu standar(CESA) selama umur rencana.NilaiLendutan dapat diperoleh dari hasil pengujian alat Benkelman Beam. Penelitian ini bertujuan untuk mengetahui hubungan antara pengukuran kondisi permukaan jalan dengan nilai lendutan “Benkelman Beam. Dari hasi survei tersebut didapatkan tingkat kondisi jalan yang perlu dilakukan overlay dan nilai lendutan balik pada setiap segmen, selanjutnya nilai lendutan yang diperoleh untuk menentukan tebal overlay  yang dibutuhkan. Dari pengujian lendutan dengan alat Benkelman Beam dihasilkan nilai lendutan rata-rata 0,15. Berdasarkan grafik pemicu konseptual nilai tersebut menyatakan bahwa ruas jalan Perintis Kemerdekaan perlu dilakukan Pemeliharaan Rutin dan Lapis tambah non struktural.Kata kunci : Benkelman Beam, Overlay, Perkerasan Lentur